2020
DOI: 10.1007/s10840-020-00896-7
|View full text |Cite
|
Sign up to set email alerts
|

T-wave inversion as a manifestation of COVID-19 infection: a case series

Abstract: Purpose Cardiac involvement with COVID-19 infection has become evident by elevated troponin, cardiac arrhythmias, ST segment elevation, myocarditis, fulminant heart failure, and sudden cardiac death. We aimed to describe the association of COVID-19 and T-wave inversion (TWI) in a large case series. Methods We conducted an observational, retrospective study of confirmed COVID-19 cases with at least one electrocardiogram (ECG) in a large hospital in New York City (March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…The multivariate analysis revealed that prolonged QTc on presentation was independently associated with an increased risk of mortality in COVID‐19 ( p = 0.001). This finding has rarely been reported and could easily have been overlooked 3,14 . Romero et al demonstrated that new T‐wave inversion in COVID‐19 was associated with mortality 14 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The multivariate analysis revealed that prolonged QTc on presentation was independently associated with an increased risk of mortality in COVID‐19 ( p = 0.001). This finding has rarely been reported and could easily have been overlooked 3,14 . Romero et al demonstrated that new T‐wave inversion in COVID‐19 was associated with mortality 14 .…”
Section: Discussionmentioning
confidence: 95%
“…This finding has rarely been reported and could easily have been overlooked. 3,14 Romero et al demonstrated that new T-wave inversion in COVID-19 was associated with mortality. 14 The ECGs reproduced in their manuscript to illustrate this T-wave inversion also demonstrate marked prolongation of the QTc, although this finding was not remarked upon and the interval was apparently not measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though troponin elevation above the 99th percentile of the upper reference limit is considered the central marker of “myocardial injury,” mild elevation between 0.05 and 1 is often non-specific and associated with non-vascular etiologies such as strain, myocyte necrosis and increased cell membrane permeability ( 11 13 ). Indeed, mild Troponin elevation was a frequent finding in our cohort, present in 31% of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, a recent study had demonstrated that T wave inversion is highly frequent finding in patients with COVID-19, conferring increased risk for mortality and particularly when accompanied by Troponin elevation (10). Though troponin elevation above the 99th percentile of the upper reference limit is considered the central marker of "myocardial injury, " mild elevation between 0.05 and 1 is often non-specific and associated with non-vascular etiologies such as strain, myocyte necrosis and increased cell membrane permeability (11)(12)(13). Indeed, mild Troponin elevation was a frequent finding in our cohort, present in 31% of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%